Keloid: multicentre study on the outcome of multimodality management - Chong, Nicholas Franklin Tow Mun (2020)
Introduction: Keloids are benign hyperproliferative growths of dermal fibroblasts characterized by the excessive deposition of extracellular matrix components, especially collagen, fibronectin, elastin, proteoglycans, and growth factors such as TGF-β. They remain difficult to improve despite a plethora of advocated treatment strategies frequently observed in daily clinical routine. Hence, multimodality treatment is often recommended for optimum control of the disease. This study aims to assess the outcome of intralesional triamcinolone acetonide (TAC) injections with concurrent scar massage in management of keloid scarring in our setting, in order to optimise its management in the local population. Methods:This is a prospective observational study conducted in the Reconstructive Sciences Unit, Hospital UniversitiSains Malaysia (Hospital USM) and the Department of Plastic & Reconstructive Surgery, Hospital Kuala Lumpur (HKL). This study involves the collection of POSAS scores from patients with keloid scars while they undergo treatment with intralesional TAC injections with concurrent scar massage.The POSAS scores is used to analyse the treatment outcome of keloid scars in the Malaysian population. Results:The one-way repeated measures ANOVA was applied to assess the outcome of treatment. All patient and observer components of the POSAS showed improvements in keloid scars between the initial and conclusion visit. Patient components: pain (39.04%), itch (36.45%), thickness (30.40%), stiffness (23.62%), irregularity (20.50%), colour (10.18%) (NS), overall (20.50%) and total (26.74%). Observer components: vascularity (44.19%), relief (36.94%), thickness (34.67%), surface area (34.55%), pliability (34.22%), pigmentation (16.58), overall (34.63%) and total (33.93%). The overall and total patient scores showed significant improvements by mean differences of 1.43 (p=0.016) and 9.50(p<0.001)respectively, while the overall and total observer scores showed significant improvements by mean differences of 2.00 (p<0.001) and 9.30 (p<0.001) respectively. Conclusion:The treatment of keloid scars with intralesional TAC injections and concurrent scar massage is found to be effective in the Malaysian population. These improvements were demonstrated through the use of the POSAS. Cosmetic concerns appear to predominate the help-seeking behaviour of patients, with a persistence of these characteristics at the end of the study. Clinical assessment, however reveal contour deformity to be tenacious, rather than colour inconsistency. Nevertheless, in totality, the combination of intralesional TAC with scar massage is a cost effective yet clinically potent regime effective in improving keloid scars in the local setting.